ChemInform Abstract: Rh‐Catalyzed Cyclization of 3‐Aryloxycarbonyldiazonaphthoquinones for the Synthesis of β‐Phenylnaphthalene Lactones and Formal Synthesis of Pradimicinone. Issue 3 (29th December 2015) - Kitamura, Mitsuru; Takahashi, Shuhei; Okauchi, Tatsuo
Abstract: This method is used in the preparation of pradimicinone precursor (X).